The Role of Supply Chain Management in Tourism Industry of the Community in Kelimutu National Park - Bungtilu Laiskodat, Viktor; Kameo, Daniel; Utami, Intiyas; Therik, Wilson (ExcelingTech, 2020)
Evaluation of different elements of tourism in different purposes has become a necessity, as a result of evaluation of these elements leads to optimal allocation of resources to development programs, rural tourism is one of the main forces in improving and economic growth of villages. In such circumstances, evaluating the rural tourism supply chain is considered as one of the most important strategies for the development of a village. Tourism Supply Chain Evaluation deals with how a tourism product is produced, when and how it reaches tourists, and what the feedback is. This paper is investigated the effectiveness of supply chain management in truism for the Waturaka village, which has succeeded in increasing the village's original income with tourism. The process of developing the supply chain system for village's potential to generate authentic village income experiences dynamics and challenges. This research aims to identify the challenges facing the village of Waturaka and explain the success factors of rural tourism development. The research method is a qualitative design by conducting in-depth interviews with village officials, the community, tourism awareness groups and traditional leaders in Village. The results showed that an increase in village original income could occur because of the truism supply chain process that initiated the development of rural tourism. The success of the tourist village is also due to traditional leaders.